Insulin Resistance in Early Rheumatoid Arthritis Is Associated with Low Appendicular Lean Mass. (28th August 2017) - Müller, Raili; Kull, Mart; Lember, Margus; Põlluste, Kaja; Valner, Annika; Kallikorm, Riina
Abstract : In established rheumatoid arthritis (RA), the presence of insulin resistance (IR) is well proven but, in the early stage of the disease, data are inconclusive. We evaluated the presence of IR and associations with body composition (BC) parameters among early RA (ERA) and control subjects. The study group consisted of 92 ERA and 321 control subjects. Using homeostatic model assessment of IR (HOMA-IR), the cut-off value for IR was 2.15. 56% of the ERA patients and 25% of the controls had IR. Of the BC parameters, patients with early RA had less fat-free mass and appendicular lean mass (ALM). In multivariable model, ERA group (b -Coefficient) (4.8, CI: 2.6–8.8), male gender (7.7, CI: 2.7–22.1), and fat mass index (1.2, CI: 1.1–1.4) were associated with IR. Insulin-resistant ERA patients had higher inflammatory markers and higher disease activity. In the multivariable model in the ERA group, IR was associated with male gender (b -Coefficient) (7.4, CI: 153–34.9), high disease activity (6.2, CI: 1.7–22.2), and lower ALM (0.03, CI: 0.001–0.97). IR develops in the early stage of RA in the majority of patients. IR is more common among males and is associated with RA disease activity and lower ALM.